The Influence of Empathetic Leadership and School Culture on Teachers’ Psychological Well-Being: A Meta-Analysis Approach - Darno Raharjo; Widodo Widodo; Merry Lapasau; Hasbullah Hasbullah; Hendro Prasetyono (Jurnal Penelitian Pendidikan IPA, 2026)
Teachers’ psychological well-being was a crucial component in creating an educational environment that supported optimal and effective learning. The psychological condition of teachers influenced the quality of classroom interactions, work motivation, emotional resilience, and professional stability. Various interpersonal and organizational factors contributed to this well-being, including empathetic leadership demonstrated by school leaders and the school culture that shaped teachers’ daily work environment. This study aimed to examine the influence of empathetic leadership and school culture on teachers’ psychological well-being through a meta-analysis approach that provided a more objective and comprehensive estimation of the overall effect. A total of 25 quantitative empirical studies that met the inclusion criteria were analyzed using a random effects model. The results indicated that empathetic leadership had a positive and significant relationship with teachers’ psychological well-being (r = 0.460, p < 0.001). School culture also showed a positive and significant relationship (r = 0.449, p < 0.001). These findings emphasized the importance of emotionally supportive leadership practices and collaborative school environments in maintaining teachers’ mental health. This study provided empirical evidence and practical recommendations for strengthening leadership practices and improving school culture to enhance teachers’ psychological well-being sustainably.